James S. Frazer, Commissioner, The Revised Statutes of Indiana: Containing, Also, the United States and Indiana Constitutions and an Appendix of Historical Documents Page 371-372, §1985 - (:unkn) unknown (General Publisher, 1881)
Prohibited the concealed carry of any dirk, pistol, Bowie-knife, dagger, sword-cane, or any other dangerous or deadly weapon. Also prohibited the open carry of the same with intent to injure another. Violators fined any sum not exceeding five hundred dollars
--
Keywords: CARRY - CONCEALED